Comparison of compressive strength between three different plates for mandibular angle fractures fixation - Negreiros Lyrio, Mariana C. [UNESP]; Monnazzi, Marcelo Silva [UNESP]; Moraes, Marcio de [UNESP]; Vieira, Eduardo Hochuli [UNESP]; Reis, José Mauricio Nunes [UNESP]; Pereira-Filho, Valfrido Antonio [UNESP] (Elsevier, 2013)
The present study aims to compare three types of internal fixation for fractures of the mandibular angle. Mechanical testing was performed on replicas of polyurethane hemimandibles sectioned at the angle region to simulate a fracture and fixed with three different hardwares. Fixation devices enrolled on this survey included the grid plates with and without an intermediate bar and the method described by Champy and colleagues in 1978 and the sample consisted of 10 hemimandibles for each group. Vertical loadings were applied on each hemimandible and recorded after a vertical displacement of 3 and 5 mm. Statistical analysis was made by means of the variance analysis (ANOVA) and the Duncan test with a significance level of 5%. The Champy technique showed a statistically significant increased resistance when compared to the grid plates after vertical displacements of 3 and 5 mm. The results of this survey suggest that the Champy technique, when compared to the grid plate positioned at the middle of the mandibular bone (placement site selected for this study), is more resistant than the grid plate and that the inclusion or not of an intermediate bar to the grid plates does not improve its resistance after linear vertical loadings.
Keywords: Bite force; Bone plate; Compressive strength; Mandibular fracture